State as Shareholder: Comparison Between Indonesia and Singapore - Cesaria, Bunga Dita Rahma (Justice Voice, 2025)
This article examines the role of the state as a shareholder under Indonesia’s reformed State-Owned Enterprises (SOE) Law, comparing it with the approach in Singapore. The aim is to provide a preliminary discussion on the corporate governance of Indonesian SOEs under the new legal framework, while addressing gaps in existing literature on SOE governance, particularly in Asia. Using a juridical normative method with a comparative approach, the research reveals key differences in the regulation of the state’s role as a shareholder in both countries. These differences are explored from the perspectives of the state’s economic motivations, the separation of its regulatory and shareholder functions, and its involvement in SOE investment and management decisions. The article argues that no single corporate governance model is inherently superior. As a result, the future success of Indonesian SOEs under the reformed law, in comparison to Singapore’s model, remains an open question for further study.